A novel assessment system of toxicity and stability of CuO nanoparticles via copper super sensitive Saccharomyces cerevisiae mutants. (December 2020) - Chen, Xueqing; Zhang, Ruixia; Sun, Jing; Simth, Nathan; Zhao, Miaoyun; Lee, Jaekwon; Ke, Qinfei; Wu, Xiaobin
Abstract: CuO nanoparticles (CuO-NPs) toxicity in organisms is contributed mainly through the copper uptake by both the ionic and nanoparticle form. However, the relative uptake ratio and bioavailability of the two different forms is not well known due to a lack of sensitive and effective assessment systems. We developed a series of both copper resistant and hyper sensitive Saccharomyces cerevisiae mutants to investigate and compare the effects of CuO-NPs and dissolved copper (CuCl2 ), on the eukaryote with the purpose of quantitating the relative contributions of nanoparticles and dissolved species for Cu uptake. We observed the toxicity of 10 mM CuO-NPs for copper sensitive strains is equal to that of 0.5 mM CuCl2 and the main toxic effect is most likely generated from oxidative stress through reactive oxygen species (ROS) production. About 95% CuO-NPs exist in nanoparticle form under neutral environmental conditions. Assessing the cellular metal content of wild type and copper transporter 1( CTR1 ) knock out cells showed that endocytosis is the major absorption style for CuO-NPs. This study also found a similar toxicity of Ag for both 10 mM Ag-NPs and 0.2 mM AgNO3 in the copper super sensitive strains. Our study revealed the absorption mechanism of soluble metal based nanomaterials CuO-NPs and Ag-NPs as well as provided a sensitive and delicate system to precisely evaluate the toxicity and stability of nanoparticles. Highlights: Our study developed a novel and accurate system to evaluate the toxicity and stability of CuO-NPs and Ag-NPs. About 95% CuO-NPs exist in nanoparticle form under neutral environmental conditions. The toxicity of CuCl2 for copper super sensitive strains is 20 times higher than that of CuO-NPs. The toxic effect of high intracellular concentrations of CuO-NPs is likely due to oxidative stress and endocytosis is the major absorption style for CuO-NPs. The toxicity of AgNO3 for copper super sensitive strains is 50 times higher than that of Ag-NPs.